Comparison of Different Dosimetric Indices for Volumetric Arc Modulated Treatment Planning Using 2 Different Treatment Planning Systems: A Feasibility Study for Total Body Irradiation - Reena Kumari; Budhi Singh Yadav; Pankaj Kumar (Asian Pacific Journal of Cancer Care, 2023)
Objective: To compare two different treatment planning systems (TPSs) for plan quality and to check the feasibility of VMAT TBI on the Elekta linear accelerator ‘Versa HD’. Methods: Ten clinical VMAT TBI plans were replanned in Monaco TPS version 5 for retrospective dosimetric analysis and to check the feasibility of treatment delivery in Elekta Versa HD. A dose of 12 Gy in 6 fractions was prescribed to cover 95% PTV. The OARs were the lungs, kidneys, heart, liver, and brain. Dosimetric optimization and calculation were performed in Monaco TPS with a statistical uncertainty of 1%, 2 mm grid. The chosen criterion for plan evaluation and comparison was based on plan quality, dosimetric indices like conformity and homogeneity index, and OAR doses. The comparison of time for optimization, monitor units, and beam on time was also analyzed. Pre-treatment verification using Octavious phantom and gamma analysis using Low’s method with a dose difference of 3% and distance to agreement 3mm criteria was done. The dosimetry of 2 VMAT TBI plans were compared using Wilcoxon signed rank test. Result: The calculated average maximum and mean doses of the PTV were 14.3321Gy and 12.235Gy for eclipse; and 14.428Gy and 12.198Gy for the Monaco system, respectively. The planning time in Monaco was approx. 4.5–6hrs compared to 14–18hrs for Eclipse TPS. Statistically significant difference was observed between the results of 2 TPSs in terms of monitor units, mean doses to lungs, kidneys, heart, and liver and planning time (P < 0.05). However, calculated p values for HI, CI, and brain for both VMAT TBI plans were not statistically different. Conclusion: The study showed the feasibility of VMAT TBI for VERSA HD as it offers faster, better optimization in a single target compared to the Eclipse.